2014
DOI: 10.1016/j.ultsonch.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Quality properties of pre- and post-rigor beef muscle after interventions with high frequency ultrasound

Abstract: The delivery of a consistent quality product to the consumer is vitally important for the food industry. The aim of this study was to investigate the potential for using high frequency ultrasound applied to pre- and post-rigor beef muscle on the metabolism and subsequent quality. High frequency ultrasound (600kHz at 48kPa and 65kPa acoustic pressure) applied to post-rigor beef striploin steaks resulted in no significant effect on the texture (peak force value) of cooked steaks as measured by a Tenderometer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…Nevertheless, effects of HIU on meat are contradictory. Some authors have reported a significant increase in tenderness (Alarcón‐Rojo et al, ; Chang, Xu, Zhou, Li, & Huang, ; Hu et al, ; Smith, Cannon, Novakofski, McKeith, & O'Brien, ), while others have found no effect (Got et al, ; Lyng, Allen, & McKenna, ; Sikes, Mawson, Stark, & Warner, ) or even negative effects (Ozuna, Puig, García‐Pérez, Mulet, & Cárcel, ). Some of this contradiction can be attributed to the inconsistency in time used when applying HIU.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, effects of HIU on meat are contradictory. Some authors have reported a significant increase in tenderness (Alarcón‐Rojo et al, ; Chang, Xu, Zhou, Li, & Huang, ; Hu et al, ; Smith, Cannon, Novakofski, McKeith, & O'Brien, ), while others have found no effect (Got et al, ; Lyng, Allen, & McKenna, ; Sikes, Mawson, Stark, & Warner, ) or even negative effects (Ozuna, Puig, García‐Pérez, Mulet, & Cárcel, ). Some of this contradiction can be attributed to the inconsistency in time used when applying HIU.…”
Section: Introductionmentioning
confidence: 99%
“…Likely, only some durations provide ideal conditions creating structural changes in meat fibers. In meat, frequency ranges of 15 kHz–2.6 MHz, intensity ranges of 0.29–10 W cm −2 , and time ranges of 15 s to 90 min, individually applied per side, have been reported (Alarcon‐Rojo, Carrillo‐Lopez, Reyes‐Villagrana, Huerta‐Jiménez, & Garcia‐Galicia, ; Got et al, ; Lyng et al, ; Pohlman, Dikeman, & Kropf, ; Sikes et al, ). However, the widest used frequencies in foods are in the range of 20–1 mHz and intensities >10 W cm −2 (Ashokkumar, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power‐ultrasound has also been reported to reduce muscle fiber diameter and thermal stability of collagen in beef and suggested hypothesis by the authors was that improvement in tenderness was the effect of ultrasound on collagen characteristics (Chang, Xu, Zhou, Li, & Huang, ). Several studies conducted on the use of low‐intensity ultrasound have reported no beneficial effect on meat tenderization (Lyng, Allen, & Mckenna, , ; Sikes, Mawson, Stark, & Warner, ) indicating the importance of the intensity when using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Sikes et al. () also observed the effects on metabolism with no improvement in tenderness of the pre‐rigor beef semimembranosus muscle, indicating the potential of the process for the treatment of DFD (dark, firm, and dry) meat by metabolic process modifications (Terefe et al., ). Ozuna, Puig, García‐Pérez, Mulet, and Cárcel () studied the effect of high‐intensity ultrasound on the textural properties of brined pork longissimus dorsi muscle.…”
Section: Introductionmentioning
confidence: 99%